Estimativas de famílias pobres e de baixa renda para o Cadastro Único - Pedro Herculano Guimar\~aes Ferreira de Souza; Rafael Guerreiro Osorio (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The municipal targets for the coverage of poor and low-incomes families in the Cadastro Único have remained unchanged for the past 12 years. Updating these targets is complicated by the existence of substantial differences between the Cadastro Único and national household surveys. This paper proposes a novel method for harmonizing these discrepancies and generating municipal targets, as well as lower and upper bounds to account for statistical uncertainty and data constraints. This method integrates data from the National Household Sample Survey (PNADC), the 2022 Demographic Census, and the Cadastro Único itself in four sequential steps, which refine previous initiatives. The first step entails the calculation of cross-sectional targets and the corresponding lower and upper bounds at the regional level. The second step involves the apportionment of the estimates to municipalities. The third step comprises adjustments to account for income volatility and limited sample coverage in household surveys. The final step reconciles the estimates with the population figures derived from the 2022 census. At the national level, our findings suggest that there are 20.6 million poor families, a figure that is similar to the 20.8 million families that are currently receiving benefits from the Bolsa Família Program, but lower than the 23.5 million poor families currently registered on the Cadastro Único. Now, approximately 70% of Brazilian municipalities are between the lower and upper bounds, while just over a quarter are above the ceiling. Almost 40% of the excess poverty is concentrated in the municipalities of the state of Rio de Janeiro. Our estimate for low-income families is 32 million, which is higher than the 28 million families with updated records in the Cadastro Único, mid-2024. Roughly, half of the municipalities are between the floor and the ceiling, while the other half are below the lower bound. Around half of Brazilian municipalities are situated between the lower and upper bounds, while the other half are below the floor.
Keywords: D31; H53; I32; O54; 330; Bolsa Família Program; Single Registry; conditional cash transfers; targeting; Brazil